Ameliorative effects of ganoderma lucidum (Reishi) on testicular tissue of rats exposed to bisphenol A - Acisu, T. C.; Akarsu, S. A.; Sonmez, M.; Yuce, A.; Ceribasi, S.; Cinkara, S. Dayan; Gur, S. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2024)
Bisphenol A (BPA), an endocrine disrupting chemical, is an environmental toxicant widely used in the production of polycarbonate plastics, epoxy resins and paints. Ganoderma lucidum (GDL) is a plant with biological activities widely used in Chinese medicine. The present study aims to determine the effects of GDL against testicular dysfunction in rats exposed to BPA. For this purpose, a total of 24 Sprague Dawley rats, 6 rats in each group, were used in the study. Rats were administered 25 mg/kg/bw BPA and 300 mg/kg/bw GDL by oral gavage for 8 weeks. After the treatments, the rats were sacrificed, and testicular tissues were removed. One of the testes was used for biochemical analyses and the other for histopathologic examinations. The caudal part of the epididymis was trimmed, and semen was obtained. As a result, BPA increased MDA level in blood and testicular tissue, while it decreased CAT, GPx activity and GSH level. GDL treatment provided protection from the impaired oxidant balance (p<0.001). Furthermore, BPA caused decreased epididymal sperm motility and density, vesicular seminalis weight and blood testosterone levels, increased testicular and epididymal tissue weight (p<0.001). Histopathological examination revealed that BPA caused narrowing in testicular tubules and apoptosis, decreased germinal cell thickness and androgen receptor number. It was determined that GDL administration preserved testicular histology. As a result, it was determined that BPA caused toxicity in the testicular tissue of rats, whereas GDL administration was ameliorative.
Keywords: bisphenol A; ganoderma lucidum; rat; sperm; toxicity